Studies on the systematics and taxonomy of the genus Hylaeus F. (8) Revision of the Afrotropic subgenus Hylaeus (Deranchylaeus) Bridwell (Hymenoptera: Anthophila, Colletidae) - Dathe, Holger H. (Zootaxa, 2014)
The Afrotropic subgenus Deranchylaeus of the colletid bee genus Hylaeus is revised for the first time on the basis of all the available type material. Here, 28 new synonymies were detected: Prosopis flaviscutum Alfken and Hylaeus graaffi Cockerell = H. curvicarinatus (Cameron); H. microstictus Cockerell = H. dregei (Strand); H. bequaertianus Bridwell and H. ogilviei Cockerell = H. gabonicus (Vachal); P. immarginata Alfken and H. abjunctus Cockerell = H. krebsianus (Strand); H. absonulus Cockerell and H. reditus Cockerell = H. lightfooti Bridwell; H. subreditus Cockerell = H. lineaticeps (Friese); H. tinctulus extensicornis Cockerell = H. perater Cockerell; P. corpana Warncke and H. rhodognathus Cockerell = H. promontorii Meade-Waldo; P. atriceps Friese, P. atriceps var. major Strand, H. sanctus Cockerell, H. sublucens Cockerell, H. varians Cockerell, H. tenuis var. dominae Cockerell, H. punctiferus Cockerell, P. totana Warncke and H. multifarius Eardley & Urban = H. robertianus (Cameron); H. simulans Cockerell = H. rugipunctus (Alfken); H. simplex (Bingham), H. simplior Meade-Waldo, H. perdensus Cockerell and P. postica Warncke = H. tenuis (Alfken); H. kasindensis Cockerell = H. xanthostoma (Alfken). Lectotypes were designated for Prosopis alfkeni Friese, P. atriceps Friese, P. curvicarinata Cameron, P. flaviscutum Alfken, P. gabonica Vachal, P. rugipuncta Alfken, P. tenuis Alfken and P. xanthostoma Alfken. The following 12 new species are described: H. (Deranchylaeus) amharicus sp. n. ♀; bernhardi sp. n. ♂; camerunensis sp. n. ♂♀; chimani sp. n. ♂; eardleyi sp. n. ♂♀; gessianus sp. n. ♂♀; izikosalis sp. n. ♀; nottoni sp. n. ♀; oromialis sp. n. ♂♀; pamelae sp. n. ♀; paulyi sp. n. ♂♀ and venustus sp. n. ♂. Keys for the identification of males and females of all species are provided.